1993
DOI: 10.1177/002221949302600303
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with Learning Disabilities at Risk? Emotional Well-Being, Depression, Suicide

Abstract: As recently as 5 years ago, very little information on the emotional well-being of adolescents with learning disabilities (LD) was available. However, a great deal of research has been conducted recently and some of the implications are unnerving. Research on self-concept, attributions, anxiety, depression, and suicide among adolescents with LD is examined for the purpose of detecting consistency of indicators concerning these emotional and developmental variables. The research indicates that the emotional dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
2
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(99 citation statements)
references
References 51 publications
(93 reference statements)
2
87
2
6
Order By: Relevance
“…Several studies (cf. Huntington & Bender, 1993;Jensen et al, 1993;Prior et al, 1999;Cluver et al,2009) indicate the co-existence of anxiety, depression, post-traumatic stress or emotional problems on the one hand, and learning disabilities in children on the other. Rates of school drop-out, substance abuse and subsequent delinquency have also been found to be significantly higher in children with learning disabilities than in those without learning disabilities (Cameron & Dent, 2003;Morrison & Cosden, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (cf. Huntington & Bender, 1993;Jensen et al, 1993;Prior et al, 1999;Cluver et al,2009) indicate the co-existence of anxiety, depression, post-traumatic stress or emotional problems on the one hand, and learning disabilities in children on the other. Rates of school drop-out, substance abuse and subsequent delinquency have also been found to be significantly higher in children with learning disabilities than in those without learning disabilities (Cameron & Dent, 2003;Morrison & Cosden, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Huntington and Bender (1993) reviewed evidence on more widely defined learning-disabled (LD) samples. They con-Study are available from a number of ages.…”
Section: Introductionmentioning
confidence: 99%
“…Within integrated classrooms, students with special needs are more likely to be nominated by their nondisabled peers for aggressiveness and disruptiveness, and they are also more likely to be rejected by their schoolmates (Farmer, 2000;Farmer & Hollowell, 1994). Studies have also shown that students with learning disabilities are at a greater risk for depression and suicide (Bender, Rosenkrans, & Crane, 1999;Bender & Wall, 1994;Huntington & Bender, 1993;McBride & Seigel, 1997).…”
mentioning
confidence: 99%